Analisis Multikultural Humanistik dalam Membentuk Budaya Toleransi Peserta Didik Pada Pembelajaran Pendidikan Agama Islam - Agustina, Rifka Sri; Mas’ula, Wahibatul (AFKARINA: Jurnal Pendidikan Agama Islam, 2022)
AbstracThis study aims to determine the development of humanistic multicultural education in learning Islamic Religious Education and the analysis of Islamic religious education in a culture of tolerance at SMP 3 Situbondo. This research used a qualitative research method with a purposive sampling technique approach. The research results show that the development of humanistic multicultural values in learning Islamic religious education is carried out according to the objectives, materials, methods and evaluation of learning in the syllabus. The culture of tolerance is implemented through the learning of Islamic religious education and manners through the attitude and example of Islamic religious education teachers and teachers of other subjects.